2019
DOI: 10.12659/msm.916209
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Attenuates IL-1β Induced Matrix Catabolism, Apoptosis and Inflammation in Rat Chondrocytes and Inhibits Cartilage Degeneration

Abstract: BackgroundChondrocyte dysfunction and apoptosis are 2 major features during the progression of osteoarthritis. Catalpol, an iridoid glycoside isolated from the root of Rehmannia, is a valuable medication with anti-inflammatory, anti-oxidative, and anti-apoptotic effects in various diseases. However, whether catalpol protects against osteoarthritis has not been investigated.Material/MethodsTo assess the role of catalpol in osteoarthritis and the potential mechanism of action, chondrocytes were treated with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…In past decades, a growing body of evidence has revealed that apoptosis plays an important role in the ropivacaine induced neurotoxicity (Chen Y et al, 2019; Wang S et al, 2019;Wen X et al, 2019), most studies have demonstrated that ropivacaine may induce neurotoxicity via activating apoptosis and up-regulating apoptosis-related genes. These were consistent with our previous ndings that ropivacaine could induce apoptosis of PC12 cells which was related to the activation of the Fas / Fasl signaling pathway (Zeng Y et al, 2019).…”
Section: Introductionsupporting
confidence: 93%
“…In past decades, a growing body of evidence has revealed that apoptosis plays an important role in the ropivacaine induced neurotoxicity (Chen Y et al, 2019; Wang S et al, 2019;Wen X et al, 2019), most studies have demonstrated that ropivacaine may induce neurotoxicity via activating apoptosis and up-regulating apoptosis-related genes. These were consistent with our previous ndings that ropivacaine could induce apoptosis of PC12 cells which was related to the activation of the Fas / Fasl signaling pathway (Zeng Y et al, 2019).…”
Section: Introductionsupporting
confidence: 93%
“…Chondrocytes are the only cell type in cartilage, and chondrocytes respond to injury, maintain tissue homeostasis, and maintain cartilage homeostasis by regulating the synthesis and enzymatic breakdown of the ECM [28,29]. There is accumulating evidence of an association between cartilage degeneration and chondrocyte apoptosis [30,31]. Chondrocyte apoptosis leads to the destruction of articular cartilage, which is characteristic of OA [32,33] and plays a critical role in the onset and progression of OA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol, which is an iridoid glycoside extracted from Rehmannia glutinosa, has an anti-ischemic effect (18)(19)(20)(21). it has been suggested that catalpol could effectively protect promyelinating oligodendrocytes from apoptosis and myelination defects.…”
Section: Discussionmentioning
confidence: 99%